Effect of magnesium addition in aluminum A1100 casting process on its hardness - Rigel, Muhammad; Murjito, Murjito; Mamungkas, Mohamad Irkham (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2024)
This study investigated the effect of adding magnesium to the hardness of aluminum A 1100 in the casting process using Rockwell testing. Aluminum A 1100 is known to have relatively low mechanical strength but has good corrosion properties. The addition of magnesium is done to increase the hardness of aluminum A 1100. Aluminum A 1100 samples are made with variations of adding 0%, 2%, 4%, and 6% by weight. Casting is carried out using prepared sand molds, and the resulting A 1100 aluminum specimens are tested by Rockwell testing. The findings could guide industries that use aluminum A 1100 in applications requiring higher hardness, such as automotive or manufacturing. In addition, this research may serve as a foundation for further studies on the effect of magnesium addition on the mechanical properties of aluminum A 1100 using different test methods.